ARTIFICIAL INTELLIGENCE AND HUMAN CREATIVITY: SYNERGY OR SUBSTITUTION? - Buzurukov, Azbarkhuja (University Research Base, 2025)
The rapid evolution of artificial intelligence (AI) has raised significant questions about its relationship with human creativity. While early views portrayed AI as a potential threat to original human expression, emerging research reveals a more complex and collaborative dynamic. This paper investigates how AI can both augment and challenge human creativity across various domains, including the arts, workplace innovation, and cognitive processes. Drawing on several recent academic studies, the article explores generative AI, narrow AI, and hybrid human-AI creative systems. Key findings suggest that when AI tools are designed to support rather than replace human inputs, they can stimulate divergent thinking, provide novel inspiration, and democratize creative expression. However, the delegation of creative tasks to AI also risks diminishing intrinsic human motivation and altering traditional definitions of creativity. Through a structured analysis grounded in current interdisciplinary research, this study examines when AI serves as a collaborator and when it risks becoming a substitute. The article concludes by proposing a framework for ethical and effective integration of AI into creative workflows, emphasizing human-centered design and transparency. This nuanced perspective supports a vision where artificial and human intelligence complement each other, expanding the boundaries of what can be imagined and produced.